Die approximative Funktionalgleichung für die heckesche Zetafunktion des Reel—quadratischen Zahlkörpers - Matuliauskas, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Матуляускас. Приближенное функциональное уравнение ζ-функции Гекке вещественного квадратичного поля A. Matuliauskas. Realaus kvadratinio skaičių kūno Heke ζ-funkcijos artutinė funkcionalinė lygtis